Underwater 3D Mapping of Ashmore Reef, Australia - Parnum, Iain; Woods, Andrew; Belton, David; Helmholz, Petra (Geohab 2023, 2023)
Ashmore Reef Marine Park was establish in 1983. It hosts Mesophotic Coral Ecosystems (MCEs). To understand these important marine ecosystems further, a Schmidt Ocean Institute cruise (FK210409) of Ashmore Reef’s MCEs on the R/V Falkor, led by the Australian Institute of Marine Science (AIMS) and the West Australian Museum (WAM), was carried out in April 2021. As part of this study, vessel-based multibeam echosounder data, and still images captured from a Remotely Operated Vehicle (ROV) were collected around Ashmore Reef (Australia) at depths between 50 and 500 m. This study aimed to create 3D models of the MCEs from the still images, and georeference them within the multibeam bathymetry.